Oil and gas activity in the high north: Economic opportunities and political dependencies - Harsem, Øistein Breiland (University of Tromsø, 2013)
Papers 1, 2 and 3 of this thesis are not available in Munin: 1. Øistein Harsem, Arne Eide and Knut Heen: 'Factors influencing future oil and gas prospects in the Arctic', Energy Policy (2011), vol. 39(12):8037–8045. Available at http://dx.doi.org/10.1016/j.enpol.2011.09.058 2. Øistein Harsem, Knut Heen, Joao Rodrigues and Terje Vassdal: 'Oil exploration and sea ice projections in the Arctic' (manuscript). 3. Dag Harald Claes and Øistein Harsem: 'The interdependence of European-Russian energy relations' (manuscript). The aim of this thesis is to analyze what drives Arctic oil and gas activity, and the political effects of the oil and gas industry in the high north. Based on existing political economy theories, four different articles explore these questions by using different methodological approaches. The main findings are that while the potential for a large increase in Arctic oil and gas output is significant, only certain Arctic provinces may become more attractive. An Arctic oil and gas bonanza is unlikely. Further, the Arctic energy resources are to a large extent embedded in the Russian-European energy relationship, which is best characterized by interdependence. Natural gas can be used as a political instrument under specific conditions, but future developments may increase diversification of natural gas and decrease the potential of using natural gas for political purposes.